Introduction of Complete Ration Silage to Substitute the Conventional Ration at Traditional Dairy Farms in Lembang - Hasanah, U.; Permana, I.G.; Despal (Pakistan Journal of Nutrition, 2017)
Background and Objective: Unsustainable forage supply is one of the limiting factors when providing sufficient nutrients for dairy cattle. Although silage technology has been available for years, their utilization in the traditional dairy farming community of Koperasi Peternak Susu Bandung Utara (KPSBU) Lembang has not been popular. An experiment was conducted to evaluate the impact of collectively made Complete Ration Silage (CRS) to substitute the current ration used by the farmers. Materials and Methods: Three types of rations (R0, R1 and R2) were tested to substitute 0, 20 and 40% of the conventional ration. This experiment used 12 Friesian Holstein cows with initial conditions of 463.28±42.18 kg b.wt., 20±3.27 L daily milk and 1-3 lactation cycle(s) and 3.5±1.6 months in milk. The cows were grouped according to their initial body weight before being assigned to the treatments. The parameters observed in this experiment included the physical and fermentative characteristics of the CRS, nutrient contents, fermentability, digestibility and the intake of the rations. The impact that the rations had on the performances of the cows were observed in terms of manure score, milk production and quality, body weight gain, body condition score and technical and economical feed efficiencies. Results: The results showed that R2 produced significantly higher values (p<0.05) in fermentability, manure score and milk production compared to those produced by R0 and R1. There were no significant differences in feed intake, digestibility, milk production, BCS and feed efficiencies. Conclusion: It can be concluded that the substitution up to 40% of the conventional ration with CRS can be done to sustain a supply of high-quality nutrients for dairy cows kept by traditional farmer and will improve the competitive technical and economical efficiencies and have a positive impact on the dairy cows’ performance.